Ask the Experts: Gene therapy in malignant pleural mesothelioma. (February 2014) - Tagawa, Masatoshi
Dr Masatoshi Tagawa graduated with MD from the School of Medicine, Chiba University (Chiba, Japan) and completed the graduated course in Chiba University (awarded PhD) in 1984. He spent a few years in Stanford University (CA, USA) as a postdoctoral fellow and became an assistant professor at Chiba University. He then moved to Chiba Cancer Center Research Institute (Chiba, Japan) as the Head in Division of Pathology and Cell Therapy, and became a professor of Graduate School of Medicine at Chiba University. He is currently a council member of the Japan Society of Gene Therapy and International Society of Cell and Gene Therapy of Cancer. He also serves as an editor of Cancer Gene Therapy . His primary research field is molecular biology and oncology and he is currently working on mesothelioma at preclinical and clinical research levels.